Weighting method of the Fourier-kinoform synthesis - Kuzmenko, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
A new iterative Fourier transform method of synthesis of kinoforms is
presented. Two object-depended filters (an amplitude filter and a phase one) are used in
the object plane on the iterative calculation of a kinoform instead of a single (phase) filter
as usual. The amplitude filter is a system of weight coefficients that vary in the process
of iterations and control the amplitude of an input object. The advantages of the proposed
method over other ones are confirmed by computer-based experiments. It is found that
the method is most efficient for binary objects.